SUSTAINABLE PREFORMANCE CRITERIA FOR INDUSTRIAL BUILDINGS CONSTRUCTION METHOD IN EGYPT: معايير الاداء المستدام لطريقة تشييد المنشآت الصناعية فى مصر - Mahmoud Ezzat Elkotb salem, Khaled Mohmed Mohmed Heiza, Kamel Sayed Ahmed Kandeel (Journal of engineering sciences and information technology, 2021)
As for factories, they are always divided into two main parts, which are the administrative part and the part in which the industrial process takes place, which is the industrial part. The two parts may be located in one building or a building dedicated to each part may be built, depending largely on the requirements of the industry and the size of the factory. There are large differences between the use of each part and thus, resulting in large differences in the characteristics of each building. The ways of choosing the construction method for industrial building in Egypt still depend to a large extent on anecdotal evidence or simply cost- based evaluation when comparing different construction methods for industrial buildings. Therefore, there is an urgent need for holistic criteria to assist in the method of choosing the appropriate construction method for industrial buildings during the early stages (design and planning stage) of the project. By reviewing the previous literature and the requirements of the various stakeholders in the project, reviewing the Egyptian laws, whether building laws or environmental laws, as well as labor laws, and making comprehensive comparisons between the different construction methods, especially the on- site construction method and the off- site construction method, a set of 30 Sustainable Performance criteria (SPC) based on the Trip Bottom Line (TBL) were determined. A questionnaire was designed and a survey was conducted for Egyptian practitioners who have experience in either the industrial building construction industry or in off- site construction methods. The survey included contractors, consultants and owners of industrial buildings. The survey was conducted to determine their perceptions of the importance of the selected criteria. The ranking analysis of the survey results showed that there is still a low importance for social and environmental standards compared to economic criteria in the method of choosing methods for constructing industrial buildings in Egypt.